Análise de viabilidade técnica de utilização da Fibra de bananeira com resina sintética em Compósitos - Mota, Rui Carlos de Sousa (2010)
This paper aims to present the feasibility of using a composite using discarded material from the cultivation of banana tree (pseudostem), which is fibrillated together with synthetic resin replacing glass fiber to be used in structural elements that do not demand large mechanical stress such as reservoirs, troughs, domes, sewage pipes etc.. For this, there were studies about the mechanical properties of a composite made with polyester resin and fiber of banana tree (Musa sp, musac), in which the splints were removed from the pseudostem, being made fibrillation by hand, with the aid of a brush steel, followed by natural drying. After treatment for cleaning and removal of wax, the fiber was cut into pieces of approximately 60 mm to 100 mm, for, together with synthetic resin, make cards of a features fiber composite with random orientation relative to the weight of the resin. We used three different percentages of fiber (3%, 6% and 9%), in order to make a comparative study between them and what would be the one with the best performance. Were manufactured specimens of each material and then subjected to uniaxial tensile tests, three point bending, moisture absorption and thermal characteristics. The results show that, in general, the use of banana tree fiber is feasible simply by an improvement in the production process (machining of the procedure) and greater care in the manufacture of parts